Assessing Option B+ retention and infant follow-up in Lilongwe, Malawi. (February 2018) - Hauser, Blake M; Miller, William C; Tweya, Hannock; Speight, Colin; Mtande, Tiwonge; Phiri, Sam; Ball, LM; Hosseinipour, Mina C; Hoffman, Irving F; Rosenberg, Nora E
Malawi launched Option B+, a program for all pregnant or breastfeeding HIV-positive women to begin lifelong combination antiretroviral therapy (cART), in July 2011. This study characterises a portion of the continuum of care within an antenatal setting in Lilongwe. Women testing HIV-positive and having a cART initiation record at Bwaila Antenatal Clinic from July 2013 to January 2014 were included. Using logistic regression models, we analysed relationships between maternal characteristics and return for infant testing. Among 490 HIV-positive women with a cART initiation record, 360 (73%) were retained at three months. Of these, 203 (56%) were adherent. Records of infant testing were located for 204 women (42%). Women who were not retained were less likely to have an early infant diagnosis record (aOR = 0.20; 95% CI: 0.10, 0.41). Among the women retained, there was a non-significant association between maternal adherence and infant testing (OR = 1.35; 95% CI: 0.89, 2.06). Women lost at earlier continuum stages, who are at higher risk for mother-to-child-transmission, were less likely to bring infants for testing. Even with a test-and-treat program, many women did not remain in care or bring their infant for testing. Facilitating strategies to improve these measures remains an important unmet need.